Plan de negocios para la producción y comercialización de galletas a base de harina de amaranto en la ciudad de Quito - Rodríguez Moncayo, Pablo Andrés (2014)
The thesis submitted below presents a business proposal to start a company dedicated to the production and commercialization of cookies made from amaranth flour. It contains a specific and a global vision of every influential variable that interacts with the ecuadorian industry, an industry analysis was developed studying its trends and structure, the opportunities and threats that it represents. A market research was developed in both quantitative and qualitative specters in wich data was gathered from primary and secondary sources. The data was analyzed in criteria of the necessities of information that was required to find a market segment attractive enough for the company. It was found what the trends in the industry are; the preferences of witch could be the potential clients. It was also found that the product proposal has a promising acceptance in the public and that the dimensions of the market offer real opportunities. A marketing plan was also developed according with the data found in the market research, this marketing plan carries an approach to what people is expecting from a product like this, the plan offers differentiation strategies attractive to specific segments, ATL publicity mediums were not taken in account because of the vision of the product that is looking to satisfy the necessities of specifics segments witch are difficult to reach by these means. Instead it was prioritized the marketing efficiency focusing mostly all marketing efforts in the penetration of the new market, it was also developed in this chapter the name for the brank, Mikuna. Once known the marketing objectives and necessities, an operations plan was developed which was focused in the optimization of resources and the quality of the final product. The operations plan seeks to exploit the potential of this product keeping in mind the clear vision of growth and responsibility. An organization chart was generated based of the operational necessities stipulated in the operations plans, this team of professionals have to take on the startup of the company, keeping a good workplace and the promise of professional growth for each individual, this chapter contains also policies and specific functions of each member. Finally, the financial viability was determined through a financial plan witch synthesizes all the data gathered throughout the business plan, all the variables surrounding the business plan were taken in account and it was proven that the company is financially profitable within 6 possible scenarios by the first year of operations...